1990
DOI: 10.1002/app.1990.070391112
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of heterophase blends of polycaprolactam and hydrogenated polydienes

Abstract: SynopsisThe preparation, analysis, testing, and structure determination of ultrahigh impact rubbertoughened polycaprolactams (nylon 6) are described. Partially unsaturated hydrocarbon rubbers were used for this purpose. They were functionalized by reaction either in solution or in bulk with maleic anhydride to give rubbery "ene" adducts containing varying amounts of pendent succinic anhydride. Tough, rigid, thermoplastic engineering resins with notched Izod impact strengths of 750-1000 J/m were prepared by bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 16 publications
0
31
0
1
Order By: Relevance
“…The morphology of PBT/E-MA-GMA blends shown here closely resembles those of other polymer/rubber blends having low toughness. [26][27][28][29][30] With increasing E-MA-GMA content, there is a complete change in the fracture morphology, from brittle ( Figure 8 (Figure 9a), which resemble but not identical to those of fast fracture in glassy polymers. Each parabolic marking contains a flaw or heterogeneity at the locus at which the secondary fracture seems to have initiated.…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…The morphology of PBT/E-MA-GMA blends shown here closely resembles those of other polymer/rubber blends having low toughness. [26][27][28][29][30] With increasing E-MA-GMA content, there is a complete change in the fracture morphology, from brittle ( Figure 8 (Figure 9a), which resemble but not identical to those of fast fracture in glassy polymers. Each parabolic marking contains a flaw or heterogeneity at the locus at which the secondary fracture seems to have initiated.…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…From a previous study 30 on toughening PA-6 with partially unsaturated rubbers, which were functionalized with maleic anhydride, it was found that the blends consist of about 35% of a rubber-g-nylon comb-block copolymer. Our results seem to be in agreement with this since in spectrum c the characteristic peaks of maleic anhydride groups were still detected.…”
Section: Ftir Spectroscopymentioning
confidence: 98%
“…Percentagem de nitrogênio em diferentes amostras, determinadas por análise elementar CHN binária PA6/EPDM em relação à blenda PA6/EPDM/EPDMg-AM deve-se provavelmente a fraca adesão entre as fases. Os diâmetros dos domínios em blendas binárias com pequenas quantidades de EPDM-g-AM com um grau de enxerto de anidrido maleico de 1,7%, são da ordem de 0,03 a 0,60 µm, faixa considerada ideal para obtenção de materiais tenazes [18] . Entretanto, valores de resistência ao impacto Izod superiores ao valor correspondente a PA6 foram obtidos para as blendas PA6/EPDM-g-AM.…”
Section: Barra G M O Et Al -Blendas De Poliamida 6/elastômerounclassified